Penerapan Model Pembelajaran Discovery untuk Meningkatkan Keterampilan Proses Sains dan Penguasaan Konsep IPA SMP - Jurmila, Jurmila; Hunaidah, Hunaidah; Sukariasih, Luh (Jurnal Penelitian Pendidikan Fisika, 2019)
This study aims to describe the increase in students' mastery of concepts and KPS as well as the implementation of teacher learning in science learning class VIIID SMP Kartika XX-6 Kendari using the discovery model. This type of research is the PTK. The subjects in this study were all 26 students of the 2018/2019 academic year. The research data is concept mastery data obtained from tests and KPS obtained from observation sheets. The data were analyzed by using descriptive statistics. The results of data analysis showed that: 1) the mean value of concept mastery in the first cycle was 70.07 with a standard deviation of 9.34, while in the second cycle the mean value of concept mastery was 77.50 with a standard deviation of 5.55; 2) the percentage of aspects of science process skills in the first cycle was 50.55% in the sufficient category, while in the second cycle, 73.41% was in the good category; and 2) the mean value of the implementation of teacher learning in the first cycle was 2.8 and the second cycle was 3.57.